Indoor to outdoor: Transformation of Coffee Shops in Jakarta - Azkiya Nisa; Maria Regina Widhiasti; Euis Puspita Dewi (Department of Architecture Universitas Muhammadiyah Jakarta, 2022)
From the colonial period to the Covid-19 pandemic, coffee cafes in Jakarta have seen significant changes. Coffee shops as public places must adjust to the pandemic situation by reducing their operating activity to prevent the virus from spreading. This adaption process then prompts coffee industry participants to come up with ways to keep coffee consumption habits consistent, such as employing outdoor spaces that are similar to rural aspects in urban settings. This study will examine the transition of coffee shops in the new normal era of the Covid-19 pandemic, building on prior research on the meaning of traditional-modern coffee shops and the performance of interior design in coffee shops. In addition, this research aims at the meaning of open space and how it relates to consumption patterns. The research method used is a literature review with in-depth analysis in order to solve issues that are related to the subject. The findings reveal that the current open space trend is a negotiation between urban-rural and public-private places. This tendency, however, poses a dilemma in terms of the monetization of the artistic portrayal of rural components adopted by coffee shops in Jakarta.